A phase II study of gemcitabine plus nab-paclitaxel as first-line therapy for locally advanced pancreatic cancer. Issue 20 (21st May 2021) - Fukahori, Masaru; Miwa, Keisuke; Murotani, Kenta; Naito, Yoshiki; Ushijima, Tomoyuki; Sakaue, Takahiko; Tanaka, Toshimitsu; Nagasu, Sachiko; Suga, Hideya; Kakuma, Tatsuyuki; Okabe, Yoshinobu; Torimura, Takuji
Abstract : Abstract: Gemcitabine plus nab-paclitaxel (GnP) is widely used in clinical practice, despite a lack of prospective data to validate its efficacy in locally advanced pancreatic cancer (LAPC). We conducted a phase II study of GnP for LAPC to assess its efficacy and safety. We performed a single-arm, single-institution study with GnP in 24 patients with LAPC. The treatment protocol included successive administration of gemcitabine (1000 mg/m 2 ) and nab-paclitaxel (125 mg/m 2 ). The primary endpoint was the tumor overall response rate (ORR), and secondary endpoints were overall survival (OS), progression-free survival (PFS), and adverse events (AEs). The median PFS was 11.0 months, median OS was 21.2 months, ORR was 62.5%, and 37.5% of the patients had stable disease. Four (16.7%) of the patients were converted to surgical resection; 3 of these achieved R0 resection. Grade 3 to 4 AEs included hematological (neutropenia, 64%; thrombocytopenia, 12%), nonhematological (cholangitis, 16%), and sensory neuropathy (4%). These AEs were manageable and tolerable. The GnP treatment in patients with LAPC showed favorable tumor shrinkage, good toxicity profile, and enabled conversion to surgical resection in a subset of patients; therefore, GnP is an option for first-line chemotherapy in patients with LAPC.